The use of cannabis for Hyperemesis Gravidarum (HG) - Gideon Koren; Rana Cohen (BMC, 2020)
Abstract Background Hyperemesis Gravidarum (HG) responds only partially to standard antiemetic medications. Cannabis has been known to possess antiemetic effects and there are several medicinal cannabinoids used as anti -emetics for cancer chemotherapy. Its favorable use for HG has been described in social media, but not in the medical literature. Methods We evaluated 4 women with HG counseled by the Motherisk Program, before and following the use of cannabis. Using the validated Pregnancy Unique Quantification of Emesis (PUQE) scoring system and employing the Student's paired t test, we compared changes in symptoms following initiation of cannabis. Results There was a highly significant improvement in symptoms: PUQE score improved from 14.5+/− 1 to 7.5+/− 0.58(p = 0.0004). Cannabis use was associated with a significant increase in the PUQE Quality of Life scale, from 2+/− 0.82 to 7+/− 0.82 (p = 0.0012). Conclusions The results suggest that cannabis may be effective for HG, and should be studied in appropriately powered, controlled studies, fully considering potential fetal risks.